GAMBARAN PENGETAHUAN IBU TENTANG PERTOLONGAN PERTAMA KEGAWATDARURATAN DEMAN PADA BALITA DI POSYANDU SOKARAJA KULON - Nurul Fatwati Fitriana (Universitas Pahlawan, 2021)
Fever is when the body temperature rises by 38 celcius degree. Fever in children is one of the reasons parents seek medical help to treat it. Fever management is very important to reduce the negative impact caused by fever. The aims of this studi was to determine the description of parental knowledge in first aid for fever emergencies in children. This research was a descriptive study and using cross sectional approach. Sampling was done by accidental sampling and data collection using a knowledge questionnaire of fever management with 16 questions. It was analysed by univariate analysis. Out of 20 respondent, the average value of the respondent’s knowledge was 12,25, with minimum score of 8 and maximum value of 16. The result of this research shows that all respondents would measure a chlid’s temperature using a thermometer when he had a fever, take his child to seek medical help when he was sick, and do a compress with warm water on a child who has fever.